The Domination of Lady Macbeth in William Shakespeare’s Macbeth - Putera Karuniawan (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2021)
Abstract In this scientific article analyzed a classic literary work of William Shakespeare's Macbeth using Sidanius Prato's social dominance theory which described the dominance of a female figure carried out by Lady Macbeth on King Macbeth power before and after being king in Scotland. And also the theory of supporting abjections according to Julia Kristeva who describes the identity that tries to break away from a pattern of a deviant community life that is described by the appointment of Lady Macbeth and King Macbeth, and the last theory of Sigmund Freud about psychosexual (castration anxiety and penis envy) to be able to support the broader domination of figures The woman concerned with social dominance at the appointment of women and men. Analysis In this article only focuses on two figures namely Lady Macbeth and King Macbeth. The conclusion in this article is where Lady Macbeth is able to teach and affect all decisions and actions of a King Macbeth.